Uso del ichu y yeso para mejorar el confort térmico de viviendas de tapial en zonas altoandinas de la provincia de Pomabamba - Ancash - 2021 - Vega Gonzáles, Franklin Enrique (2022)
This research evaluates the thermal comfort of mud-brick houses, using ichu and gypsum in the wall covering in high Andean zones of the province of Pomabamba. The methodology was experimental; it has been taken 05 tapial houses of equal or higher than 3500msnm, subsequently it has been determined the thermal characteristics without and with the intervention of ichu and plaster in the wall covering, the average temperature per house without the intervention oscillated between (8.9  11.9°C), with an average value of 10.5°C and with the intervention had a slight fluctuation oscillating between (9.5  12.6°C), with an increase of 0. 7°C, achieving an average indoor temperature of 11.2°C, but not achieving the required minimum temperature of 17°C; while the average relative humidity per dwelling without the intervention ranged between(57  61%), with an average value of 59%, and with the intervention ranged between (62  76%), with an increase of 10%, achieving an average indoor humidity of 69%, an uncomfortable percentage, because the summer season in the Peruvian highlands is with the presence of rain. Likewise, the economic benefits according to the activities carried out generated a cost of s/33.79 per m2.